Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5623/cig2011-061
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Curvelet Transform for Building Extraction from High Resolution Satellite Imagery

Abstract: The process of automatic extraction of buildings from digital imagery has had major practical importance for many years in the area of data acquisition and updating of geographic information system (GIS) databases. This process also presents a huge scientific challenge for researchers as a result of the heterogeneous nature of the buildings, especially in the developing countries[Aytekin et al. 2009]. Several techniques were used in building extraction for satellite images in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The lake has nearly a triangular shape with elongated sides extending roughly East-West. It has a surface area of about 8 km 2 and with an average depth of 11 meters and a volume of about 90 million cubic meters of water (El-Sharkawy, 2012). It is significantly polluted; the sources of pollution are essentially the raw sewage from the city network, industrial pollution from shore-line workshops, domestic sewage from unconnected areas adjoining the shore, agricultural drainage water, and possibly marine pollution (El-Moselhy and Yassien, 2005).…”
Section: Sampling Stations Of Study Areamentioning
confidence: 99%
“…The lake has nearly a triangular shape with elongated sides extending roughly East-West. It has a surface area of about 8 km 2 and with an average depth of 11 meters and a volume of about 90 million cubic meters of water (El-Sharkawy, 2012). It is significantly polluted; the sources of pollution are essentially the raw sewage from the city network, industrial pollution from shore-line workshops, domestic sewage from unconnected areas adjoining the shore, agricultural drainage water, and possibly marine pollution (El-Moselhy and Yassien, 2005).…”
Section: Sampling Stations Of Study Areamentioning
confidence: 99%
“…Consequently, by arranging the coefficients of each level and taking the most significant part of them, this will enhance the edge information that represents the image part of interest. Then, the coefficients are reconstructed to get a new image called the edge map (Elsharkawy et al, 2011), as shown in Figure 11, where the edge parts are enhanced. Table 1 summarizes the total number of coefficient in each scale and the weight of each scale level used to reconstruct the edge map.…”
Section: Methodsmentioning
confidence: 99%
“…Direct thresholding of the edge map generated from the curvelet transforms was discussed in (Elsharkawy et al, 2011;Elsharkawy et al, 2012), for building extraction for high-resolution satellite imagery. In this research paper, an implementation of the second generation curvelet transform followed by the three main steps for the canny operator, gradient calculation, nonmaximal suppression and hysteresis, for edge detection of high-resolution satellite imagery.…”
Section: Introductionmentioning
confidence: 99%
“…Based on shape and area characteristics, buildings will be extracted from the candidate parcels. The algorithm is summarized in figure 3; more details about this technique can be found in (Elsharkawy et al, 2011b) . The second step, of the algorithm deals with the classification step.…”
Section: Methodsmentioning
confidence: 99%
“…Taking advantage of all these properties a new pixel/object-based technique is introduced to extract shadows, water, vegetation, buildings, bare soil and asphalt roads for a complex scene in Ismailia city, 120 Kms to the north-east of Cairo the capital of Egypt. The new technique integrates the classification result from three new band ratios along with edge detection algorithm using the second generation curvelet transform (Elsharkawy et al, 2011b). The band ratio section showed very good results regarding water, shadow, asphalt roads, vegetation.…”
Section: Introductionmentioning
confidence: 99%